Criminal liability for banking crime perpetrators who make false records of customer deposits (decision study number: 2644/ Pid.B /2021/PN Mdn) - Yusuf Gideon Silaban; Shulhan Iqbal Nasution (Priviet Social Sciences Journal, 2025)
The security of customer funds in banks is often problematic due to the actions of bank employees themselves, where bank employees directly involved with customer funds commit acts of embezzlement in their positions by embezzling customer funds. The problem formulated in this study is as follows: What are the legal regulations regarding Banking Crimes that make false records of Customer Deposit Funds according to the applicable laws and regulations in Indonesia? and What are the legal considerations of the Judge at the Medan District Court in imposing criminal sanctions on perpetrators of the crime of false records Case Number: 2644 / Pid.B / 2021 / PN Mdn? This study aims to discuss the criminal liability of perpetrators of false record crimes. The type of research used in this study uses normative legal research. The data collection techniques used are library research and field research. The data analysis conducted in this study was qualitative. The results of the study found that criminal liability for bank employees who commit the crime of false recording can be punished using the provisions of Article 49, paragraph (1) of the Republic of Indonesia Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking. The provisions of Article 49 of the Banking Law contain legal certainty because this article has been specifically designed for the crime of false recording, and the provisions of the Article expressly regulate the prohibition of false recording and provide threats of criminal sanctions for violators. The results of the analysis of Decision Number: 2644 / Pid.B / 2021 / PN Mdn concluded that the criminal sentence imposed on the Defendant by the Medan District Court was 5 (five) years in prison and a fine of IDR 10,000,000,000.00 (ten billion rupiah) with the provision that if the fine is not paid, it will be replaced with charges for 4 (four) months. According to the author, this sentence contains the principle of law enforcement and is in accordance with the provisions of Article 49 of the Banking Law.